Radiocesium concentrations in the lichen-reindeer/caribou food chain: Before and after Chernobyl - Robert G. White; Dan F. Holleman; Ann C. Allaye-Chan (Rangifer, 1986)
This paper reviews historical concentrations of radiocesium (Cs-137) in the reindeer/caribou food chain in Alaska. These data, along with available kinetic models which describe the movement of radiocesium through the food chain, are used to predict consequences of radioactive fallout from the Chernobyl accident which occurred in late April 1986. During the present discussion, efforts are made to directly relate the Alaskan data to the Scandinavian situation as it exists following the Chernobyl accident.